Increased Risk of Endometriosis in Patients With Lower Genital Tract Infection: A Nationwide Cohort Study. Issue 10 (March 2016) - Lin, Wu-Chou; Chang, Cherry Yin-Yi; Hsu, Yu-An; Chiang, Jen-Huai; Wan, Lei
Abstract : Abstract: Endometriosis results from the ectopic invasion of endometrial glands and stroma in the peritoneal cavity. The exact etiology of endometriosis is still unknown. It has, however, been shown that there are higher numbers of Escherichia coli in menstrual blood, and higher endotoxin levels in menstrual fluid, as well as, in the peritoneal fluid of patients with endometriosis. In this study, we aimed to determine whether lower genital tract infections could increase the risk of endometriosis. We used the Taiwan National Health Insurance database to conduct a population-based cohort study. We included patients diagnosed with inflammatory diseases of the cervix, vagina, and vulva, and a control group comprising patients matched by age, sex, and comorbidities but without inflammatory diseases of the cervix, vagina, or vulva. A total of 79, 512 patients were included in the inflammatory disease group and an equal number of control individuals were selected. The incidence of endometriosis (hazard ratio, 2.01; 95% confidence interval, 1.91–2.12; P  < 0.001) was higher among patients than controls. Cox proportional hazards models showed that irrespective of comorbidities, lower genital tract infection was an independent risk factor for endometriosis. Patients with lower genital tract infections exhibit a substantially higher risk for developing endometriosis.